Ex Vivo Perfusion Treatment of Infection in Human Donor Lungs. Issue 4 (5th January 2016) - Nakajima, D.; Cypel, M.; Bonato, R.; Machuca, T. N.; Iskender, I.; Hashimoto, K.; Linacre, V.; Chen, M.; Coutinho, R.; Azad, S.; Martinu, T.; Waddell, T. K.; et al.
Abstract : Ex vivo lung perfusion (EVLP) is a platform to treat infected donor lungs with antibiotic therapy before lung transplantation. Human donor lungs that were rejected for transplantation because of clinical concern regarding infection were randomly assigned to two groups. In the antibiotic group (n = 8), lungs underwent EVLP for 12 h with high‐dose antibiotics (ciprofloxacin 400 mg or azithromycin 500 mg, vancomycin 15 mg/kg, and meropenem 2 g). In the control group (n = 7), lungs underwent EVLP for 12 h without antibiotics. A quantitative decrease in bacterial counts in bronchoalveolar lavage (BAL) was found in all antibiotic‐treated cases but in only two control cases. Perfusate endotoxin levels at 12 h were significantly lower in the antibiotic group compared with the control group. EVLP with broad‐spectrum antibiotic therapy significantly improved pulmonary oxygenation and compliance and reduced pulmonary vascular resistance. Perfusate endotoxin levels at 12 h were strongly correlated with levels of perfusates tumor necrosis factor α, IL‐1β and macrophage inflammatory proteins 1α and 1β at 12 h. In conclusion, EVLP treatment of infected donor lungs with broad‐spectrum antibiotics significantly reduced BAL bacterial counts and endotoxin levels and improved donor lung function. Abstract : Broad‐spectrum antibiotic therapy administered during ex vivo lung perfusion significantly reduces bacterial burden and endotoxin levels and improves the lung function of donor lungs clinically declined due to infection.